A Quality Improvement Initiative to Evaluate the Effectiveness of the ABCDEF Bundle on Sepsis Outcomes. Issue 1 (January 2022) - Loberg, Rachel A.; Smallheer, Benjamin A.; Thompson, Julie A.
Abstract : Sepsis affects 1.7 million Americans annually and often requires an intensive care unit (ICU) stay. Survivors of ICU can experience long-term negative effects. This quality improvement initiative was designed to increase compliance with ABCDEF bundle elements and improve clinical outcomes. A significant improvement was seen in the completion of spontaneous awakening and breathing trials ( P = .002), delirium assessment ( P = .041), and early mobility ( P = .000), which was associated with a reduction in mortality and 30-day readmission rates. Findings were consistent with other research that demonstrated an improvement in care delivery and some clinical outcomes.